PENDIDIKAN TASAWUF SEBAGAI PSIKOTERAPI BATIN - Nurul Indana (ISLAMIDA Journal of Islamic Studies, 2024)
The problem of modern society is spiritual aridity in itself, confusion about the meaning of life. One solution is with Sufism education to treat inner problems. This research is a literature research, with the research method of documentation and the analysis used is content analysis. The results of the study state that Sufism offers advice on how to live a happy life as a solution to psychological problems. To be a happy person, you must have physical and mental health. If you do so, inner conflicts will never arise. This is due to the fact that the resulting happiness eliminates all inner thoughts.